Analisis Pengaruh Host Country terhadap Perusahaan Multinasional: Skandal “Dieselgate” Volkswagen Group di Amerika Serikat - Yoga Alghazi Ahmad; Ika Riswanti Putranti (Journal of International Relations Diponegoro, 2018)
Bargaining position is an important part in the dynamics of relations between actors in international relations. Bargaining position can be regarded as a connecting bridge for a party to show leverage and to reach the intended outcome or interest. In the case of the "dieselgate" scandal in the United States, it appears the nuances of the more dominant leverage of the United States as Host Country against the Volkswagen Group as a multinational corporation (MNC) in settling the case. The United States is a home and host for several multinational corporations (MNCs) that are engaged in the automotive industry. The big names like General Motors and Ford became representations of the power of the automotive industry in the United States. The position of the United States as a country with mature political and economic conditions, is a distinct advantage for the United States. Coupled with the conditions as mentioned, it certainly creates a special attraction for several Multinational Corporations (MNCs) in this industry to develop their business activities in the United States, not least for the Volkswagen Group.